2022
DOI: 10.1007/s00213-022-06146-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of psychotropic medication and risk of road traffic crashes: a registry-based case–control study in Denmark, 1996–2018

Abstract: Rationale Use of psychotropics is relatively prevalent amongst motor vehicle drivers because mobility is also important for persons suffering from psychiatric illness. However, medication side effects may increase the likelihood of being involved in traffic crashes. Objectives This study aimed to assess the association between the use of four types of medication (antipsychotics, benzodiazepines and z-hypnotics, antidepressants and stimulants of ADH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A recent study, however, found increased odds of vehicular crashes for individuals treated with stimulants. 41 Research supports that although drivers with ADHD who do not take medication may experience more inattention and impatience than drivers with ADHD who take medication, those taking methylphenidate committed a similar number of driving errors as those without ADHD or a history of taking relevant stimulant medications during on-road driving tests. 42 …”
Section: Discussionmentioning
confidence: 91%
“…A recent study, however, found increased odds of vehicular crashes for individuals treated with stimulants. 41 Research supports that although drivers with ADHD who do not take medication may experience more inattention and impatience than drivers with ADHD who take medication, those taking methylphenidate committed a similar number of driving errors as those without ADHD or a history of taking relevant stimulant medications during on-road driving tests. 42 …”
Section: Discussionmentioning
confidence: 91%
“…These findings are consistent with previous studies published in the literature that found associations with motor vehicle crashes and antidepressants 44 , 45 and sedatives and hypnotics. 46 , 47 Other medications that have been implicated in the literature include anticonvulsants, muscle relaxants, and anticholinergic drugs. These were either not found to be associated with driving impairment in our study or the prevalence of the drug was too small to study (eg, opioids or muscle relaxants).…”
Section: Resultsmentioning
confidence: 99%
“…General discussion about the interpretation of PM toxicology results and about stability and artifacts has been provided by Druid and Skopp (2022) and by Skopp (2022), respectively. Since case–control studies devoted to fatal drowning with drugs are generally lacking (Kevrekidis et al, 2021), results obtained from epidemiological and experimental road traffic studies (Brunnauer et al, 2021; Hayley et al, 2016; Movig et al, 2004; Olesen et al, 2022; Simmons et al, 2022) could be cautiously applied to the interpretation of drowning cases.…”
Section: Requirements For Pm Toxicology Analysismentioning
confidence: 99%